Effect of structure on oxygen diffusivity in layered oxides: a combined theoretical and experimental study - Kim, ChangSub; Park, Kyoung Won; Kalaev, Dmitri; Nicollet, Clement; Harrry L. Tuller (Royal Society of Chemistry, 2022)
Electrochemical systems based on oxide ion conduction such as solid oxide fuel cells (SOFCs) and solid oxide electrolysis cells (SOECs) provide efficient means of converting energy between chemical and electrical forms, integral to a hydrogen-based energy society. Fundamental understanding of oxygen diffusivity in solids - which can depend on defect type, concentration, as well as migration barrier - is critical in developing their key components: electrolytes and mixed ionic-electronic conducting electrodes. It has been speculated that crystal structure affects the key three factors impacting oxygen diffusion, but no such experiments have been done, without changing cation chemistries, to the best of the authors' knowledge. In this work, oxygen diffusivities in two different but related structures of lanthanum cuprate (La2CuO4+delta) thin films were measured through oxygen isotope exchange experiments and secondary ion mass spectrometry (SIMS) at multiple temperatures. We find that while oxygen diffusion is faster in a T-structured layered cuprate, it nevertheless exhibits a higher activation energy as compared to a T '-structured layered cuprate of the same cation chemistry. This seemingly contradictory phenomenon is explained by a lower oxygen defect formation energy (thus higher oxygen defect concentration) but higher defect migration barrier in the T-structure as calculated by density functional theory, offering insight towards structural design of SOFC and SOEC electrolyte and electrode materials for different target temperatures.